Spontaneous mutations of a model heterotrophic marine bacterium - Sun, Ying (ISME J, 2017)
Heterotrophic marine bacterioplankton populations display substantive genomic diversity that is commonly explained to be the result of selective forces imposed by resource limitation or interactions with phage and predators. Here we use a mutation-accumulation experiment followed by whole-genome sequencing of mutation lines to determine an unbiased rate and molecular spectrum of spontaneous mutations for a model heterotrophic marine bacterium in the globally important Roseobacter clade, Ruegeria pomeroyi DSS-3. We find evidence for mutational bias towards deletions over insertions, and this process alone could account for a sizable portion of genome size diversity among roseobacters and also implies that lateral gene transfer and/or selection must also play a role in maintaining roseobacters with large genome sizes. We also find evidence for a mutational bias in favor of changes from A/T to G/C nucleobases, which explains widespread occurrences of G/C-enriched Roseobacter genomes. Using the calculated mutation rate of 1.39 × 10(−10) per base per generation, we implement a ‘mutation-rate clock’ approach to date the evolution of roseobacters by assuming a constant mutation rate along their evolutionary history. This approach gives an estimated date of Roseobacter genome expansion in good agreement with an earlier fossil-based estimate of ~250 million years ago and is consistent with a hypothesis of a correlated evolutionary history between roseobacters and marine eukaryotic phytoplankton groups.